PENGARUH TAYANGAN NET 86 TERHADAP CITRA KEPOLISIAN REPUBLIK INDONESIA DI MATA MASYARAKAT DKI JAKARTA - Romi Syahril (Jurnal Akrab Juara, 2019)
Television or what is often called TV is one of the mass media that is very influential on society. One of the television stations that developed in Indonesia in 2015 is NET. NET. has a news program called NET. 86. The .NET program. 86 is a program cooperating with the Police to showcase the duties and humanist side of the police. The purpose of this research is to know the influence of Impression Net 86 on Polri image. This research is a quantitative research using survey method with audience population domiciled in Bandung amounted to 100 people. The sampling technique used is nonprobability sampling that is purposive sampling technique. This research uses simple regression analysis. The findings of this study indicate that Impressions Net 86 significant effect on Polri image.